Temporal dynamics in gray wolf space use suggest stabilizing range in the Great Lakes region, USA - van den Bosch, M.; Beyer, D.E.; Erb, J.D.; Gantchoff, M.G.; Kellner, K.F.; MacFarland, D.M.; Patterson, B.R.; Tack, J.L. Price; Roell, B.J.; Belant, J.L. (Biological conservation, 2024)
Species distribution models can facilitate conservation planning and action but presume species-environment relationships are stable, which is not the case for invasive or recolonizing species only partially occupying their potential distributions. This complicates our understanding of colonization and recolonization processes and their effects on species' distributions. We combined snow tracking data collected during gray wolf (Canis lupus) recolonization of the western Great Lakes region (Minnesota, Wisconsin, Michigan, USA) into six periods during 1989–2020 and used a species distribution model to assess temporal variation in wolf distribution in response to human population density and proportion of agricultural land cover. We found negative relationships between these covariates of human disturbance and wolf habitat suitability, with the magnitude of these relationships declining over time. Estimated wolf habitat increased 35 %, from 148,500 km2 in the first (1989–1994) period to about 201,000 km2 in the last (2016–2020) period, though increases in habitat declined across periods. Wolf presence was associated with increasing levels of human disturbance as recolonization progressed, demonstrating temporal variation in the relationship between wolf presence and indices of human disturbance. The western Great Lakes wolf population likely occupies most areas currently suitable and is limited by human landscape disturbances, resulting in apparent stabilization of regional wolf range. •Wolves occupied areas with higher human disturbance as recolonization progressed.•Increases in areas recolonized by gray wolves have declined over time.•Recolonization is now constrained by human disturbance, suggesting range stabilization.•Distribution models need to acknowledge dynamic landscape use of recolonizing species.